2020
DOI: 10.1002/ael2.20005
|View full text |Cite
|
Sign up to set email alerts
|

Sampling probes affect bulk density and soil organic carbon measurements

Abstract: Soil sampling equipment can be a major source of bias in soil organic carbon (SOC) stock estimations. The objective of this study was to evaluate the impact of sampling probes on soil bulk density (BD) and SOC stocks calculated using fixed depth (FD) and equivalent soil mass (ESM) methods. Soil samples were collected to 30 cm using three probes with different diameters and divided into 0-10-, 10-20-, and 20-30-cm layers. The probe with smallest diameter measured higher BD at 0-10 cm in 42% of fields and was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…These initial estimates can be refined further by using repeated soil sampling and laboratory procedures in the future. Although tracking temporal change in ρ b may be challenging given the uncertainty involved in sampling, within‐field soil heterogeneity, handling, and determination techniques (Han et al., 2016; Nemes et al., 2010; Sharma et al., 2020; Xu et al., 2016), it is expected that over sufficient time, a decent estimate and trajectory of ρ b can be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…These initial estimates can be refined further by using repeated soil sampling and laboratory procedures in the future. Although tracking temporal change in ρ b may be challenging given the uncertainty involved in sampling, within‐field soil heterogeneity, handling, and determination techniques (Han et al., 2016; Nemes et al., 2010; Sharma et al., 2020; Xu et al., 2016), it is expected that over sufficient time, a decent estimate and trajectory of ρ b can be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Soil bulk density characterizes the compaction of soil and its water permeability and is therefore an important index used to assess SOC [42]. However, the soil surface and soil bulk density are prone to change due to erosion or deposition of material, swelling or compaction, and anthropogenic activities [43]. In agreement with the findings from Gebrehiwot et al (2018) [44], our results showed that SOC stock had a significant positive correlation with soil bulk density, especially in fluvial plain area and closed floodplain (p<0.05).…”
Section: Effect Of Soil Characteristics On Soc Stockmentioning
confidence: 99%